FV 6. Striatal Microcircuit alterations in a mouse model of preclinical parkinsonism. Issue 9 (September 2016) - Baaske, M.K.; Kramer, E.R.; Meka, D.P.; Engler, G.; Engel, A.K.; Moll, C.K.
Abstract : Objective: During recent years, extensive studies in different genetic model systems have complemented conventional toxin-based dopamine depletion approaches and significantly advanced our pathophysiological understanding of familial Parkinson's disease (PD) from a molecular level to human clinical practice. One of the particular strengths of genetic models is that they open experimental windows to hitherto inaccessible presymptomatic periods in PD, allowing for an investigation of functional changes and adaptive mechanisms during very early phases of this complex neurodegenerative disorder. Mice with a loss-of-function mutation in the parkin-encoding PARK2 gene (a frequent cause of young-onset, autosomal recessive PD) display no motor symptoms, show no appreciable dopaminergic neurodegeneration but exhibit abnormalities of striatal dopaminergic neurotransmission and impaired signalling at the cortico-striatal synapse. Here, we set out to determine whether and how loss of parkin function affects neuronal activity in cortex-basal ganglia networks in vivo. Methods: To dissect the cortico-striato-pallidal circuitry in this premanifest model of PD, we performed simultaneous microelectrode recordings in motor cortex, striatum and globus pallidus of anesthetized parkin-mutant mice and controls. Results: Based on electrophysiological criteria of striatal single unit activity, we identified several presumably different striatal cell types: Medium spiny projection neurons (pMSN), tonically active neurons (pTAN – corresponding to cholinergic interneurons) and fast spiking interneurons (pFSI – a subpopulation of GABAergic interneurons). In transgenic mice, pTANs displayed significantly increased activity levels, while pFSIs showed reduced discharge rates compared to controls. Furthermore, we found evidence for a disrupted functional connectivity within the striatal FSI microcircuit. In line with the absence of motor symptoms, we observed no changes in the ongoing discharge characteristics of transgenic pMSNs and pallidal neurons. Phase locking analysis revealed elevated and phase-shifted phase coupling to slow (1–3 Hz) cortical local field potential oscillations. Unexpectedly, local field potentials recorded from striatum and globus pallidus of parkin-mutant mice robustly exhibited amplified beta oscillations. Notably, the subgroup of pFSIs showed a selective enhancement of phase coupling to these beta oscillations. Conclusions: Our findings suggest that loss of parkin function leads to amplifications of synchronized cortico-striatal oscillations in multiple frequency ranges and an intrastriatal reconfiguration of interneuronal circuits. This presymptomatic disarrangement of striatal dynamic functional connectivity may precede nigrostriatal neurodegeneration and predispose to imbalance of striatal outflow accompanying symptomatic PD.